Ternstroemia guerrerensis (Pentaphylacaceae), a new endangered cloud forest tree from Guerrero, Mexico - Alcántara-Ayala, Othón; Maradiaga-Ceceña, Francisco S.; Luna-Vega, Isolda; Alvarado-Sizzo, Hernán (Phytotaxa, 2022)
A new species of Ternstroemia, T. guerrerensis O. Alcántara-Ayala, I. Luna-Vega, F. S. Maradiaga-Ceceña & H. Alvarado-Sizzo, is molecular, phylogenetically, and morphologically described and illustrated from Guerrero, Mexico. This short tree inhabits disturbed areas of the tropical montane cloud forest (TMCF), with Magnolia vazquezii and different oaks as dominant species in the canopy. This new species is related to T. lineata subsp. lineata, but differs from the latter in the shape and apex of the leaves, peduncle length and color, petiole color, and length of the connective prolongation of the anthers.